Improvement of production of citric acid from oil palm empty fruit bunches: Optimization of media by statistical experimental designs - Bari, Md. Niamul; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (Elsevier Science, 2009)
A sequential optimization based on statistical design and one-factor-at-a-time (OFAT) method was employed to optimize the media constituents for the improvement of citric acid production from oil palm empty fruit bunches (EFB) through solid state bioconversion using Aspergillus niger IBO-103MNB. The results obtained from the Plackett–Burman design indicated that the co-substrate (sucrose), stimulator (methanol) and minerals (Zn, Cu, Mn and Mg) were found to be the major factors for further optimization. Based on the OFAT method, the selected medium constituents and inoculum concentration were optimized by the central composite design (CCD) under the response surface methodology (RSM). The statistical analysis showed that the optimum media containing 6.4% (w/w) of sucrose, 9% (v/w) of minerals and 15.5% (v/w) of inoculum gave the maximum production of citric acid (337.94 g/kg of dry EFB). The analysis showed that sucrose (p < 0.0011) and mineral solution (p < 0.0061) were more significant compared to inoculum concentration (p < 0.0127) for the citric acid production.